LA-ICP-MS Study of Impurity Ion Concentrations in Zircon - Araya Mungchamnankit,; Supanee Limsuwan,; Pongtip Winotai,; Siwaporn Meejoo, (Agriculture and Natural Resources, 2007)
Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) is surfacesensitive analytical technique for the estimation of element concentrations as well as their spatial distribution in the analyzed sample. In this work, LA-ICP-MS technique was used for analyzing the impurity ion concentrations in zircon. Because the presence of the impurity ions in the zircon usually caused the color in crystal, the zircon samples in this study are divided into three major groups i.e. untreated zircon (brown color), heat treated zircon in oxygen atmosphere (yellow color) and heat treated zircon in argon atmosphere (greenish blue color). For the first group, the most impurity ion concentrations are Fe (208.90 ppm) and Ti (91.24 ppm). For the second and third groups, there are Fe (965.88 ppm) and Mg (412.20 ppm), Fe (434.66 ppm) and Ti (109.26 ppm), respectively.